Predictors of participation restriction over a 9-year period in adults with myotonic dystrophy type 1. Issue 12 (5th June 2022) - Raymond, Kateri; Levasseur, Mélanie; Gallais, Benjamin; Richer, Louis; Laberge, Luc; Petitclerc, Émilie; Mathieu, Jean; Gagnon, Cynthia
Abstract: Purpose: For slowly progressive neuromuscular disease, prognostic approach and long-term monitoring of participation is a crucial part of rehabilitation services. To improve the prognostic approach, professionals must identify individuals at risk of having higher participation restriction. This study aimed to identify personal and environmental predictors of participation restriction over nine years in adults with myotonic dystrophy type 1 (DM1). Methods: A secondary analysis of a longitudinal design comparing baseline with a follow-up nine years later was used with a multidimensional assessment of participation and personal and environmental factors. Based on theoretical models, multiple linear regressions were used. Results: One hundred and fourteen adults with DM1 were included in the study (63.2% women; 78.9% adult onset; mean (SD) age of 43.5 (10.4) years). When age, sex, phenotype, and education were controlled for, participation restriction was predicted by a longer time to stand and walk, lower grip strength, higher body mass index, absence of perceived impact of myotonia in daily living, use of adapted transportation from community services, and perception of obstacle in physical environment ( p < 0.001, adjusted R 2 = 0.50). Conclusions: The majority of predictors of participation restriction can be advantageously modified by rehabilitation and environmental changes, such as politics targeting community services provision or physical environment and services accessibility. Implications for rehabilitation: Predictors could better inform rehabilitation professional to recognize individuals at risk of higher participation restriction over time and to target specific interventions based on a prognostic approach. Rehabilitation professionals could inform the people living with myotonic dystrophy type 1 and their relatives of the multifactorial nature of occurrence of participation restriction to diminish the "fatality" associated with a genetic progressive disorder. Predictors allow professionals to assess and intervene in the management of specific factors depending on the rehabilitation goal. Identifying individual with myotonic dystrophy with higher risk of participation restriction could help implement a long-term community based rehabilitation intervention plan targeting both personal and environmental factors.